PENCIPTAAN BUKU SEJARAH MUSIK BALADA DARI MASA KE MASA BERBASIS TEKNIK AQUAREL SEBAGAI UPAYA PENGENALAN KEMBALI PADA MASYARAKAT SURABAYA - Abadi, Nugraha Mukti; Budiardjo, Hardman; Hidayat, Wahyu (Jurnal Art Nouveau, 2016)
Abstract: Seeing the development of music in Surabaya today is very much different from the previous era , there are many musicians from Surabaya are able to vibrate with amazing work . tOne of them is Ballad music genres , there are some big names of Ballads legendary musicians from the city of Surabaya , as Gombloh , Franky Sahilatua , and Leo Kristi . But unfortunately this genre of music began to be abandoned by the people of Surabaya . Especially after Gombloh and Franky died , and Leo Kristi began to move to Bandung . This music is no longer heard in the city of Surabaya . It is also due to the absence participate publish media , in particular through the book . In this study show the history of the development of music Ballad in Surabaya in the 70s until the 2000s by using characters Ballad Surabaya musicians .Â Keywords: Passion, Illustration Book, Ballads Music, History, Social, Memories